Tugas dan Wewenang Badan Pengawas Obat dan Makanan (BPOM) dalam Rangka Perlindungan Konsumen - Abd Aziz (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Changes in production technology, international trade systems, and consumer lifestyles have increased the risks of the health and safety of consumers. Therefore, the government has formed the Drug and Food Supervisory Agency (BPOM) that has the responsibility and accountability in consumer protection. This paper aims to find out the duties and authority of BPOM in the context of consumer protection. The results of the study stated that there are several tasks attached to the Food and Drug Supervisory Agency (BPOM) which are based on Presidential Decree 166 of 2000. The powers are that protecting public health from the risk of circulation of therapeutic products, traditional medicines, complementary products, and cosmetics that do not meet quality requirements, safety, and efficacy, as well as food products that are unsafe and unfit for consumption. It also protects the public from the misuse of drugs, narcotics, psychotropic products, and addictive substances as well as risks due to the use of hazardous products and substances. BPOM also has the authority to conduct control, draft regulation and standardization, authorize industrial licensing and certification, product evaluation before being allowed to circulate, sampling and laboratory testing, investigation, and law enforcement.